Clinical impact of mineralocorticoid receptor antagonists treatment after acute coronary syndrome in the real world: A propensity score matching analysis. Issue 7 (October 2019) - Agra-Bermejo, Rosa; Cordero, Alberto; Rodríguez-Mañero, Moisés; García Acuña, Jose M; Álvarez Álvarez, Belén; Martínez, Álvaro; Álvarez Rodríguez, Leyre; Abou-Jokh, Charigan; Cid Álvarez, Belén; González-Juanatey, Jose Ramón
Background: Recent studies suggest that the benefit of mineralocorticoid receptor antagonists in the acute coronary syndrome setting is controversial. The aim of this study was to examine the current long-term prognostic benefit of mineralocorticoid receptor antagonists in patients with acute coronary syndrome. Material and methods: We conducted a retrospective cohort study of 8318 consecutive acute coronary syndrome patients. Baseline patient characteristics were examined and a follow-up period was established for registry of death, major cardiovascular adverse events and heart failure re-hospitalization. We performed a propensity-matching analysis to draw up two groups of patients paired according to whether or not they had been treated with mineralocorticoid receptor antagonists. The prognostic value of mineralocorticoid receptor antagonists to predict events during follow-up was analysed using Cox regression. Results: Among the study participants, only 524 patients (6.3%) were discharged on mineralocorticoid receptor antagonists. Patients on mineralocorticoid receptor antagonists had a different clinical and pharmacological profile. These differences disappeared after the propensity score analysis. The median follow-up was 40.7 months. After the propensity score analysis, the cardiovascular mortality and heart failure readmission rates were similar between patients who were discharged on mineralocorticoid receptor antagonists and those whose not. The use of mineralocorticoid receptor antagonists was only associated with a reduction in major cardiovascular adverse events (hazard ratio=0.83, 95% confidence interval 0.69–0.97, p =0.001). Conclusions: Our results do not corroborate the long-term benefit of mineralocorticoid receptor antagonists to improve survival after acute coronary syndrome in a large cohort of patients with heart failure or reduced left ventricular ejection fraction and diabetes. Their prescription was associated with a significantly lower incidence of major cardiovascular adverse events during the long-term follow-up without effect on heart failure development.